(untitled) - Crichton, Micheal (New York, 1999)
A Yale history professor travels back in time to 15th century France and gets stuck, unable to return to the present. His colleagues organize a rescue and on landing in France become involved in the Hundred Years War
Keywords: Quantum theory,Thuyết lượng tử,Time travel,Thời gian đi lại; Fiction,Tiểu thuyết,Fiction,Tiểu thuyết